Dynamics in Logistics First International Conference, LDIC 2007, Bremen, Germany, August 2007. Proceedings - Haasis, Hans-Dietrich.; Haasis, Hans-Dietrich.; Kreowski, Hans-Jörg.; Kreowski, Hans-Jörg.; Scholz-Reiter, Bernd.; Scholz-Reiter, Bernd. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Logistic problems can rarely be solved satisfyingly within one single scientific discipline. This cross-sectional character is taken into account by the Research Cluster for Dynamics in Logistics with a combination of economical, information and production technical and enterprise-oriented research approaches. In doing so, the interdisciplinary cooperation between university, research institutes and enterprises for the solution of logistic problems is encouraged. This book comprises the edited proceedings of the first International Conference on Dynamics in Logistics LDIC 2007. The scope of the conference was concerned with the identification, analysis, and description of the dynamics of logistic processes and networks. The spectrum reached from the planning and modelling of processes over innovative methods like autonomous control and knowledge management to the new technologies provided by radio frequency identification, mobile communication, and networking. Two invited papers and of 42 contributed papers on various subjects give an state-of-art overview on dynamics in logistics. They include routing in dynamic logistic networks, RFID in logistics and manufacturing networks, supply chain control policies, sustainable collaboration, knowledge management and service models in logistics, container logistics, autonomous control in logistics, and logistic process modelling.